2023
DOI: 10.1007/s00520-023-08025-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of referrals to specialist palliative care and remote patient triage — a cross-sectional study

Tomasz Grądalski,
Krystyna Kochan

Abstract: Purpose Choosing the optimal moment for admission to palliative care remains a serious challenge, as it requires a systematic identification of persons with supportive care needs. Despite the screening tools available for referring physicians, revealing the essential information for preliminary admission triage is crucial for an undisturbed qualification process. The study was aimed at analysing the eligibility criteria for specialist palliative care disclosed within provided referrals, expande… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In our study, we were able to gain important insights into reasons for referral, which were assessed using standardized referral forms, including patients referred mainly for social problems. These additional data, in combination with clinical information, provide valuable insights, especially considering the burden on SPC and the potential role of general home care, social support, and long-term care facilities [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we were able to gain important insights into reasons for referral, which were assessed using standardized referral forms, including patients referred mainly for social problems. These additional data, in combination with clinical information, provide valuable insights, especially considering the burden on SPC and the potential role of general home care, social support, and long-term care facilities [19].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a recent study, Gradalski and Kochan (2023) compared referral forms with the documentation of 300 patients referred to SPC and found that half of the referrals did not have sufficient information to justify prequalification on the basis of the documentation alone. As a result, the authors recommended that referral forms should be expanded to include a checklist of typical patients' concerns [19].…”
Section: Introductionmentioning
confidence: 99%